Starlikeness and Convexity of Generalized Struve Functions - Nihat Yagmur; Halit Orhan (Abstract and Applied Analysis)
We give sufficient conditions for the parameters of the normalized form of the generalized Struve functions to be convex and starlike in the open unit disk.